The Health Educational Virtual in Providing Breastfeeding Support During Corona Virus-19 (Covid-19) Pandemic in Indonesia - Tetti Solehati; Amalia Rizqi Sholihah; Yanti Hermayanti; Cecep Eli Kosasih (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
COVID-19 is a highly contagious and pathogenic viral infection. To determine the effect of health education through online media on the knowledge and skills in breastfeeding during the Covid-19 pandemic. The research was conducted with a pre-experimental design with totaling 103 people. Chi-Square Test performed data analysis. The results showed that there was an effect of intervention on knowledge (p=0.003), but no effect of intervention on skills (p=0.001). Information messages provided through online media effectively increase the knowledge and skill of women of childbearing age in breastfeeding during the Covid-1 pandemic.